Wijsman hyperspaces: subspaces and embeedings - Cao, J; Junnila, HJK; Moors, WB (Elsevier, 2011)
In this paper, topological properties of Wijsman hyperspaces are investigated. We study the existence of isolated points in Wijsman hyperspaces. We show that every Tychonoff space can be embedded as a closed subspace in the Wijsman hyperspace of a complete metric space which is locally R.